The ‘Meat Cooking Paradox’: Why raw and rare meat still appeals – insights from a mouse model - Yoriko Sato; Yorimune Oki; Naohisa Nakao; Reina Matsunaga; Daisuke Sato; Yusuke Komiya; Shin-ichi Adachi; Yusuke Sato (Applied Food Research)
Meat palatability is influenced by cooking methods, with some cultures favoring minimally processed meat. Using a mouse model, we investigated preferences between raw and cooked meat, focusing on traditional Japanese preparations. Food choice tests revealed that mice consistently preferred raw horse meat and minimally processed beef, regardless of texture, over cooked alternatives. This preference was specifically driven by water-soluble compounds, suggesting the presence of key palatability factors altered during thermal processing. While these findings do not directly reflect human dietary preferences, they offer valuable insights into the fundamental sensory and biochemical mechanisms underlying meat palatability. Further research including human sensory evaluations is needed to determine whether similar mechanisms influence human meat preference.